Estimation of secondary production of the Faro/Ancão artificial reefs - Moura,Ana (2011)
The secondary productivity of reef epifauna is one of the least investigated aspects in artificial reef research. During the first 12 months after the deployment of the Faro/Ancão (Algarve, Portugal) artificial reef, we assessed the effect of substratum orientation on the secondary production of epibenthos, using the Boysen-Jensen method. Whenever the method could not be applied, secondary production was estimated by the P/B ratio. The results showed that the epibenthic production was higher on the horizontal surface throughout the study. However, at the end of the study period, the mean production showed similar values. The horizontally oriented surfaces showed a mean production between 128 and 103 g m-2 yr-1, while at the vertical surfaces the mean production varied between 103 and 98 g m-2 yr-1. Furthermore, the mean annual production was extrapolated for all the Algarve artificial reef complex,and we concluded that after one year of deployment theses artificial reefs were able to generate around 5 MT of epibenthic fauna.